Autoinducer-2-mediated quorum sensing partially regulates the toxic shock response of anaerobic digestion. (1st July 2019) - Xiao, Yeyuan; Yaohari, Hazarki; Zhou, Zhongbo; Sze, Chun Chau; Stuckey, David C.
Abstract: This study discovered a strong correlation between the autoinducer-2 (AI-2)-mediated quorum sensing (QS) with the performance of a submerged anaerobic membrane bioreactor during its recovery from a pentachlorophenol (PCP) shock: a decrease in AI-2 levels coincided with a reduction in volatile fatty acid concentrations, and corresponded significantly to a decrease in the relative abundance of Firmicutes, and to an increase in the relative abundance of Bacteroidetes and Synergistetes. Further batch experiments with the addition of an AI-2-regulating Escherichia coli mutant culture showed that a reduction in AI-2 levels resulted in the highest biogas production rate during a PCP shock. In contrast, an increase in AI-2 levels via addition of the E. coli wild type strain or an AI-2 precursor showed no obvious effects on biogas production. These results suggest that the AI-2 level in anaerobic sludge was governed primarily by Firmicutes, and the AI-2-mediated QS partially regulates the toxic shock response of anaerobic sludge via tuning the activities of Firmicutes and Synergistetes. A decrease in the AI-2 level might reduce acetogenesis and favor hydrogenotrophic methanogenesis, thus resulting in less VFA accumulation and higher methane production during the PCP shock. This study is the first of this type that exploits the role of quorum sensing in the toxic shock response of anaerobic sludge; it demonstrates a novel approach to shortening the recovery period of anaerobic processes via manipulating the AI-2-mediated QS. Graphical abstract: Image 1 Highlights: AI-2 QS in anaerobic digestion was primarily governed by the fermenting bacteria. AI-2 and VFA levels decreased concurrently during the recovery from a PCP shock. The reduction in AI-2 correlated with a decrease in Firmicutes/Bacteroidetes ratio. Elevating AI-2 had no obvious effects on anaerobic digestion under a PCP shock. Quenching AI-2 improved resilience of anaerobic digestion to a PCP shock.